2006
DOI: 10.1016/s0022-5347(05)00876-1
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Male and Female Sexual Dysfunction is High Following Surgery for Rectal Cancer

Abstract: Objective: To measure sexual function and quality of life (QOL) after rectal cancer treatment. Summary Background Data: Previous studies on sexual function after rectal cancer treatment have focused on males and have not used validated instruments. Methods: Patients undergoing curative rectal cancer surgery from 1980 to 2003 were administered a questionnaire, including the Female Sexual Function Index (FSFI) or International Index of Erectile Function (IIEF), and the EORTC QLQ-C30/CR-38. Multiple logistic regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
192
4
10

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(221 citation statements)
references
References 20 publications
15
192
4
10
Order By: Relevance
“…Although studies show that the overall quality of life of survivors is quite good (especially in long-term survivors) [16][17][18], a significant proportion of patients remain at risk for persistent or worsening symptoms, including symptoms related to sexual health [19]. Although much of this work has been done in breast cancer survivors [19][20][21][22][23], emerging literature shows similar figures affected for survivors of gynecologic cancer [17,[24][25][26] and other cancer types [27][28][29][30].…”
Section: Sexual Health As a Survivorship Issuementioning
confidence: 99%
See 1 more Smart Citation
“…Although studies show that the overall quality of life of survivors is quite good (especially in long-term survivors) [16][17][18], a significant proportion of patients remain at risk for persistent or worsening symptoms, including symptoms related to sexual health [19]. Although much of this work has been done in breast cancer survivors [19][20][21][22][23], emerging literature shows similar figures affected for survivors of gynecologic cancer [17,[24][25][26] and other cancer types [27][28][29][30].…”
Section: Sexual Health As a Survivorship Issuementioning
confidence: 99%
“…Beyond gynecologic and breast cancer, other surgical approaches have also been evaluated specifically as they affect sexual health; for example, both primary excision and mesorectal excision performed for rectal cancer result in a high rate of sexual dysfunction that approaches 60% [29,30]. Additional data suggest that patients who underwent colectomy for colorectal cancer that required placement of an ostomy (in the past or presently) were at significant risk for sexual dysfunction and distress related to body image [27].…”
Section: Surgerymentioning
confidence: 99%
“…In the field of malignant rectal neoplasms, radical resection, consisting of anterior resection with total mesorectal excision (TME) when feasible and abdominoperineal resection (APR) when mandatory, represents the best curative treatment. Nevertheless, these procedures are burdened with a consistent morbidity rate, including genitourinary and sexual dysfunction (30-40%) [1][2][3][4], anastomotic leakage (5-17%) [5], and long-term functional bowel disturbance [6]. Up to 40% of patients experience perineal wound complications and long-term discomfort following APR, while stoma and stoma appliance-related complications occur in up to 66%.…”
Section: Introductionmentioning
confidence: 99%
“…Ameda et al [23] reported that postoperative EF was a serious complication, even in complete nerve preservation [22]. Hendren et al [34] also reported that a high rate of sexual dysfunction is detected after rectal cancer excision, despite the use of nervepreserving techniques. The incidence of erectile dysfunction (ED) depends on the extent of resection, which may be reduced with nerve preservation [28].…”
Section: Sexual Functionmentioning
confidence: 99%